Rapid Hippurate Hydrolysis Method for Presumptive Identification of Group B Streptococci - Hwang, Mei-Na (1975)
A rapid test to detect the hydrolysis of sodium hippurate by beta-hemolytic streptococci within 2 h was developed. All group B streptococci tested were positive using this method and all other groups were negative.